Analisis Faktor-Faktor yang Berpengaruh terhadap Kinerja Auditor pada Kantor Akuntan Publik di Semarang - Prihatin, Emy; Purbandari, Theresia; Handayani, Dwi (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2017)
This study aims to demonstrate empirically the effect of audit structure, role conflict, role ambiguity, understanding of good governance, leadership styles, organizational culture, and organizational commitment to performance auditor in public accounting firm in Semarang. The data collection is done by spreading the questionnaire directly to the respondent. The sample in this study was 39 staff auditors who worked on 11 KAP in Semarang in 2015, with the criteria for having a minimum education level S1 Accounting, and a minimum term of one year. The sampling technique used was purposive sampling. Hypothesis testing using multiple linear regression analysis with SPSS version 17. The results showed that the variables of leadership style and organizational commitment positively affects the performance of auditors. While the audit structure, role conflict, role ambiguity, understanding of good governance, and organizational culture does not affect the performance of auditors.